Glucoraphanin conversion into sulforaphane and related compounds by gut microbiota - Dmytriv, Tetiana R.; Lushchak, Oleh; Lushchak, Volodymyr I. (Frontiers in Physiology, 2025)
Glucosinolate glucoraphanin, common in cruciferous vegetables, is a biologically stable precursor of isothiocyanates, such as sulforaphane and erucin, potent activators of Nrf2 signaling coordinating an adaptive response to oxidative stress. Sulforaphane is formed by the hydrolysis of glucoraphanin by a plant enzyme called myrosinase, which is inactivated in the stomach of mammals. Since the latter do not have enzymes possessing myrosinase-like activity, glucoraphanin can be metabolized by the gut microbiota, to sulforaphane, sulforaphane-nitrile, glucoerucin, erucin, and erucin-nitrile. Emerging evidence suggests that variations in gut microbiota composition significantly influence the efficiency and outcome of glucoraphanin metabolism, while sulforaphane itself may reciprocally modulate gut microbiota composition and functionality. This review examines the bidirectional interactions between glucoraphanin, sulforaphane, and gut microbiota. We assume that sulforaphane alleviates intestinal inflammation and oxidative stress maintaining intestinal homeostasis and gut barrier integrity. Besides, the role of sulforaphane in breaking the vicious cycle of oxidative stress and gut dysbiosis is reported, demonstrating the potential of dietary isothiocyanates to support gut barrier function.